Expectativas de futuros professores de matemática sobre a prática docente - Lasso, Aristeu Alvarenga (2007)
This research aims to investigate what the undergraduates from a mathematics teacher education program expect from their future teaching practice, the schools, their future students and their future pairs, besides potential changes in these expectations depending on their stage on the program. Our academic referencing is based on researches by João Pedro da Ponte, Dario Fiorentini, Francisco Imbernón, Maurice Tardif, and Claude Lessard. These authors have written works on initial teacher education and on teaching practices and knowledge. Students in the first, second and third years answered a 27-item questionnaire with three open questions, the results of which were processed by Excel and afterwards by the software CHIC an essential tool to deduce the types of connection between the students answers and their own profile. Our results show that students in their first year have positive expectations towards their future profession and those in the last year or those who had already teached in primary or secondary levels have few positive expectations towards teaching as a career